Laju Penetrasi Korosi pada Material Alternatif Bangunan Kapal - Prantasi Harmi Tjahjanti; Eko Panunggal; Darminto Darminto; Wibowo Harso Nugroho (Jurnal Teknik Mesin (Sinta 3), 2014)
Corrosion is the event of a material damage due to undesired interactions between material and environment. Corrosion is a natural phenomenon that cannot be avoided, but that can be done is to control the corrosion process by pressing the corrosion penetration rate, so that the expected lifespan and quality durable material. Ship building alternative material used is a composite material with aluminum alloy matrix AlSi10Mg(b) a ship building materials based on European Nation (EN) Aluminum Casting (AC)-43100, and written EN AC-43100 (AlSi10Mg(b)), and mixed with reinforcement of ceramic materials is silicon carbide treatment that has been expressed by the chemical formula SiC*. Overall in writing EN AC-43100 (AlSi10Mg(b)) + SiC*. The purpose of research is to determine the rate of corrosion resistance in this composite material. Corrosion testing performed is wet corrosion test and dry corrosion. Wet corrosion test is immersion  in liquid hydrochloric acid (HCl), sodium hydroxide (NaOH), sodium chloride (NaCl), and the fluid pH = 1, 3, 5, 7, 9, 11, 13. The treatment of dry testing conducted in 2 temperature, room temperature ~270C and 1000C temperature. The results showed that immersion in liquid HCl, and the fluid pH 1, experiencing the highest rate of corrosion penetration. While the highest corrosion penetration rate in the treatment of dry corrosion test was obtained at temperatures higher than room temperature. Overall it appears that the addition of SiC*, can reduce the rate of penetration of corrosion and composite materials EN AC-43100 (AlSi10Mg(b)) +15 SiC* is a good material in the face of corrosion attack, because it has the corrosion penetration rate is lower than the standard that allowable is <0.5 mm / yr.